Application of Albion Process™ on a Complex Feed Containing Base and Precious Metals - Laurie McDonnell (Instituto de Ingenieros de Minas del Peru, 2022)
As reserves of high-grade, easily accessible ores decline, it is becoming increasingly important to treat complex feeds and recover multiple target metals, and to identify approaches that will achieve this is a cost-effective manner. Hydrometallurgical treatment of sulphide based material allows for a balance between costs, recovery, and flexibility in final product selection. Glencore Technology’s hydrometallurgical solution to the treatment of sulphide ores is the Albion Process™, comprising two main steps. The first step involves ultra-fine grinding using the IsaMill™, which minimises the potential for passivation of the leaching sulphide and increases surface area for oxidation during the Albion Process™ leach. The second step is the oxidation of the finely ground sulphide concentrate utilising the HyperSparge™ for oxygen injection in Glencore Technology’s Oxidative Leach Reactors (OxiLeach™).